Activities of a New Fluoroketolide, HMR 3787, and Its (Des)-Fluor Derivative RU 64399 Compared to Those of Telithromycin, Erythromycin A, Azithromycin, Clarithromycin, and Clindamycin against Macrolide-Susceptible or -Resistant Streptococcus pneumoniae and S. pyogenes - Nagai, Kensuke (American Society for Microbiology, 2001)
Activities of HMR 3787 and RU 64399 were compared to those of three macrolides, telithromycin, and clindamycin against 175 Streptococcus pneumoniae isolates and 121 Streptococcus pyogenes isolates. HMR3787 and telithromycin were the most active compounds tested against pneumococci. Telithromycin and RU 64399 were equally active against macrolide-susceptible (MICs, 0.008 to 0.06 μg/ml) and -resistant S. pyogenes isolates, but HMR 3787 had lower MICs for ermB strains.